THE DEVELOPMENT OF ENGLISH LEARNING MEDIA BASED ON ANDROID APPLICATION ON MATERIAL COMPLIMENTS TOWARD STUDENTS’ OF 10TH GRADE SENIOR HIGH SCHOOL - Herdina Utami; Prih Febtiningsih; Wandi Syahfutra (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
The purpose of this study was to develop English learning media based on an Android application for X SMA compliments material, as well as to determine the quality of media products. This study uses Research and Development (R&D) research and the model used is the ADDIE Development model which consists of 5 stages namely Analysis, Design, Development, Implementation and Evaluation. The data analysis technique used is feasibility and quality the media obtained with the instrument in the form of a questionnaire. This product has been validated by material experts, media experts. The results of the validation show that material experts obtain an average of 4.77 which is included in the "Very Good" criteria, for the validation results of media experts obtain an average of 4.56 in the "Very Good" category. The developed media was tested on 26 class X SMA Muhammadiyah 1 Pekanbaru. Based on the acquisition results these data indicate that Android-Based English Learning Media in Material Compliments is suitable for use as a learning resource for high school students. In trial with students obtaining a result of 4.61 which is included in the "Very Good" criteria. It can be concluded that this android-based application product can increase student motivation and achievement and is suitable for use in the learning process.